Understanding the self-efficacy of students using te ao Māori concepts in AS91925 : a mixed methods study : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Education at Massey University, Manawatu, New Zealand - Youmans Seward, Jennifer (Massey University, 2024)
Aotearoa New Zealand’s NCEA qualification has undergone recent changes, with Change 2 of the Review of Achievement Standards stating that mātauranga Māori is to have equal status with other forms of knowledge. This change has led to the incorporation of mātauranga Māori, such as the use of te ao Māori concepts as a lens with which to analyse film in English classes, in NCEA assessments for the first time in 2024. Drawing on Vygotsky’s (1978) socio-constructivist theory, this paper focusses on how students experience using te ao Māori in AS91925 to add to the current literature on self-efficacy and its relationship with culture. This mixed methods study, conducted in an inner-city girls’ school, explored the student experience and their perception of their self-efficacy through an online survey and follow-up interviews. Findings indicate that for students who identify culturally as Māori, self-efficacy is perceived as high in this assessment. For non-Māori cultural groups, self-efficacy in AS91925 is perceived diversely due to a range of social and educational factors.
Keywords: 390104 English and literacy curriculum and pedagogy (excl. LOTE, ESL and TESOL); 450811 Te mātauranga Māori i roto i te mātauranga (Mātauranga Māori in education)